1970
DOI: 10.1111/j.1365-2494.1970.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Silage and Milk Production, a Comparison Between Grass Silages Made With and Without Formic Acid

Abstract: Two grass sUages made in June and two made in September, all from the same field, were compared in a 16-week winter-feeding experiment with 12 Ayrshire cows. The silages were fed ad lib. with a supplement of barley and groundnut eake. One of the sUages made in June and one made in September had been treated with \ gallon of formie acid per ton of herbage when cut, whereas the other two silages were untreated. The contents of digestible organic matter in the sQage DM made with and without the acid additive were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
4
2

Year Published

1971
1971
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 7 publications
6
31
4
2
Order By: Relevance
“…The lower butterfat percentage of convert from ME (NAS-NRC, t966), assuming an enelgy value of 5000 kcal/kg w(ight chmge (Bath el al., 1965 _ _There is agreement between the present results and those of Derbyshire and Gordon (1970) and Castle and Watson (1970) …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The lower butterfat percentage of convert from ME (NAS-NRC, t966), assuming an enelgy value of 5000 kcal/kg w(ight chmge (Bath el al., 1965 _ _There is agreement between the present results and those of Derbyshire and Gordon (1970) and Castle and Watson (1970) …”
Section: Resultssupporting
confidence: 81%
“…Castle and Watson (1970) also showed an increase in intake of formic acid-treated silages over untreated.…”
Section: Resultsmentioning
confidence: 94%
“…Practical experience and experimental results (Castle and Watson, 1970;Peoples and Gordon, 1989;Heikkilä et al, 1998;Khalili et al, 2005) have suggested inferior intake and production potential of RG silages compared to those made from PG. This effect may partly have been due to analytical problems as at least in vitro pepsin cellulase method overestimates the regrowth silage digestibility, unless separate correction equations are used for PG and RG grass material ( (Huhtanen et al, 2006a).…”
Section: Comparison Between the Harvestsmentioning
confidence: 95%
“…Further, in these studies the season (primary growth vs. regrowth) effects have often been confounded by differences in digestibility and silage fermentation characteristics. Castle and Watson (1970) and Khalili et al (2005) observed that silage intake and milk production were higher with silages made from the primary growth than from the regrowth of grass, but in both cases, regrowth silages were lower in digestibility. However, Peoples and Gordon (1989) and Heikkilä et al (1998) used regrowth grass silages of similar or higher digestibility than in primary growth and yet silage intake and milk production were higher when silage made from primary growth was fed.…”
Section: Introductionmentioning
confidence: 93%
“…Volatile fatty acid treatment of silage has been used in Europe for a number of years to produce high quality silage without wilting the crop before ensiling (Drysdale 1968), Castle and Watson (1970) 105-lU (Jan, 1973) silage (Waldo et al 1968(Waldo et al , 1969(Waldo et al , and 1971 To determine moistrlre content, silage samples were dried at 72 C using a forced hot-air drying oven.…”
Section: Introductionmentioning
confidence: 99%